Praxis or Talk about Praxis? The Concept of Praxis in Ecclesiology - Schmiedel, Ulrich (Ecclesial practices, 2016)
Churches are in crisis. The turn to praxis in ecclesiology appears to attend to the current crisis; yet, the appearance might be deceptive. Since post-liberal ecclesiologies – such as John Milbank’s – consider neither quantitative-empirical nor qualitative-empirical accounts of concrete churches, the turn might be assessed as a turn to talk about praxis instead of a turn to praxis. Confronting Milbank’s concept of praxis with the ecclesiology of Ernst Troeltsch (1865–1923), I argue that Troeltsch allows for accounts of concrete churches since he conceptualises the identity of Christianity not as a proposition but as a project. Hence, praxis is the criterion for the evaluation of concepts of identity. Both churches and reflections on churches are to be ‘elasticised’ in order to attend to the current crisis.